GRAIN YIELD ADN YIELD COMPONENTS OF CORN AS INFLUENCED BY HARVESTING MOISTURE - & Alkazaali, Baktash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted during spring and fall seasons, 2015 , at the fields of Field Crop Department – College of Agriculture –University of Baghdad. The objective was to study grain yield and yield components of corn in next generation as influenced by harvesting moisture in the first generation . In spring season 2015 , seeds of the variety 2018 was planted using 75 cm between rows and 25 cm within the rows. When moisture of the ear grains reach the first treatment (37-42%), ten ears were harvested. Ear harvesting dates were performed manually when the grains had 37-42%, 34-36% , 30-33% , 25- 28% and 19-22% moisture content. Then, the grains were naturally dried to 15.5 %. In fall season 2015 , varietal trail was carried out with the five treatment materials , using Randomized Complete Bock Design , with four replicates . The results revealed significant differences among treatments for all the studied traits . The highest number of grains (614 grains ear-1) and (4224 grains m-2), were produced from plants grown from seeds with (25-28)%, which significantly differs from other treatments . The highest grain weight ( 266 mg), grain yield (159.46 g.plant-1) and ( 10.70 t.ha-1) , were produced from the plants at the moisture content (19-22)% . It could be conclude , that the suitable corn grain moisture harvest for production seeds for next generation are (19-22)% .